The Effect of Coping Stress and Social Support on Learning Motivation - Lita Zahrah Nurahmah; Rismawati Suci; Nawasyi Asyari; Lucky Purwantini (Profesional Muda Cendekia Publishing, 2023)
As a student, you must be able to manage the demands of problems that are considered burdensome for the individual. Meanwhile, learning motivation is an internal and external impulse in a person who is studying to carry out behavioral changes, generally with some indicators or elements that support it. Social Support as an interpersonal exchange where an individual provides assistance to another individual. The purpose of this study was to determine the effect of Coping stress and Social Supoort on Learning Motivation in 134 students. This research uses quantitative methods with the distribution of questionnaires through Google From then links are distributed to students. The data analysis technique of this study uses the statistical technique of spearman Rho. The sample technique of this study uses Purposive Random Sampling. Based on the results of the multiple linear regression test, Coping Stress and Social Support for Learning Motivation showed a result of F 79.803 with a significant value of p = 0.000 where (p< 0.05). which means that Ha is accepted and H0 is rejected so, that there is a significant influence of Coping Stress and Social Support on Learning Motivation with the value of the dertetermination coefficient (R) is 0.741 and the coeffesient (R2) is 0.549, this value shows the contribution of the influence of Coping Stress and Social Support on Learning Motivation by 74.1% while 25.9% is influenced by other variables or other factors that were not studied in this study.